Cryopreservation of Newborn Mice Adrenal Cell Suspension: 1. Effect of DMSO Concentration as a Component of Cryoprotective Medium - Tamarina, I. V.; Bozhok, G. A.; Gurina, T. M.; Gubina, N. F.; Bondarenko, T. P. (Problems of Cryobiology and Cryomedicine, 2024)
Influence of DMSO concentrations as a component of cryopreservative medium on viability, survival and functional activity of the newborn mice adrenal cells after freeze-thawing cycle has been established in this study. Maximal values of viability (63.7; 66.7%) and survival (78.3; 95.7%) are observed after freezing of newborn mice adrenal cell suspension (ACS) in the medium with 15 and 20% DMSO. Regardless the high values of ACS viability and survival after freeze-thawing cycle, none of the DMSO concentrations being used was not capable to preserve proper post-thaw cell proliferation and hormone production.